Optimizing Nitrogen Fertilization Regimes for Sustainable Maize (Zea mays L.) Production on the Volcanic Soils of Buea Cameroon - Christopher Ngosong; Victorine Bongkisheri; Clovis B. Tanyi; Lawrence T. Nanganoa; Aaron S. Tening (Advances in Agriculture)
Nitrogen (N) fertilizer is commonly used to improve soil fertility and maize production in Cameroon, but high cost and potential environmental effects have necessitated site-specific N fertilization regimes that are adapted to particular soil and crop types. A field experiment was conducted with five N application rates (control–0, 50, 100, 150, and 200 kg N ha−1) to determine optimum rate for best maize yield with limited effect on soil acidification. The soil residual N ranged from 0.18 to 0.36% across N application rates and increased at higher application rates with the highest in 150 and 200 kg N ha−1. Soil C/N ratio ranged from 7.5 to 15.5 across N rates with the highest in control, which decreased at higher N application rates. Soil pH ranged from 4.7 to 5.4 across N rates, with the lowest in 200 kg N ha−1 rate. Maize grain yield and cob length ranged from 7.1 to 10.3 t ha−1 and from 14.5 to 18 cm across N rates, respectively, with the highest in 150 and 200 kg N ha−1. Maize 1000-grain weight ranged from 380 to 560 g across N application rates with the highest in 100, 150, and 200 kg N ha−1. Significant negative correlations occurred between soil pH and maize yield or 1000-grain weight. Maize N use efficiency decreased sharply at higher N application rates, as demonstrated by a strong negative correlation between the N-Partial Factor Productivity and total soil N. Overall, the lower soil pH at higher N application rates highlights the potential for deleterious effects of N fertilizer inputs on arable soils, which may eventually affect crop productivity, thereby suggesting lower N fertilization regimes between 50 and 100 kg N ha−1 as the optimum for maize production on the volcanic soils of Buea.